(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Road traffic incidents (RTIs) are a leading cause of death worldwide, particularly in low- and middle-income countries. The number of fatal traffic accidents rises sharply in tandem with the number of vehicles on the road, from motorcycles to large trucks. In order to identify common injury patterns, demographic trends, and clinical outcomes, this retrospec tive analysis looks at the autopsy records of 236 fatal RTA patients. The results indicate that long bone fractures and cranio-cerebral traumas are the leading causes of death, particularly for men between the ages of 19 and 45. The gender and age differences in these injury categories are evident in the higher prevalence of organ ruptures and crush injuries in older age groups. The leading cause of death for victims of RTAs was head injury (170 out of 236 cases) followed by shock and haemorrhage (30 out of 236 cases). Thus, the study highlights the necessity of improved trauma treatment programs and focused preventative measures.